Preponderance of bacterial isolates in urine of HIV-positive malaria-infected pregnant women with urinary tract infection - Osho, Patrick; Adejuyigbe, Ebunoluwa; Ebhodaghe, Blessing Itohan; Ajibade, Kwashie; Ako, Nai (2023)
journal Article;1600 pages,